2018
DOI: 10.2807/1560-7917.es.2018.23.30.1700775
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and resistance phenotypes of carbapenemase-producing Klebsiella pneumoniae in Greece, 2014 to 2016

Abstract: on behalf of the study collaborators. Epidemiology and resistance phenotypes of carbapenemase-producing Klebsiella pneumoniae in Greece, 2014. Euro Surveill. 201823(31):pii=1700775. https://doi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
48
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 31 publications
8
48
1
3
Order By: Relevance
“…In the present study, 100% and over 50% of the KPCproducers were resistant to temocillin according to the systemic and urinary breakpoints, respectively. Our data are however in line with a report from Greece describing low temocillin activity against KPC-producers: 97.3% and 42% were resistant according to systemic and urinary breakpoints, respectively [24]. The low number of KPC-producing isolates is a limitation of the study, but the set of clinical isolates tested was representative of the population of KPC-producing isolates cultured from clinical specimens between 2010 and 2017 in Poland.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, 100% and over 50% of the KPCproducers were resistant to temocillin according to the systemic and urinary breakpoints, respectively. Our data are however in line with a report from Greece describing low temocillin activity against KPC-producers: 97.3% and 42% were resistant according to systemic and urinary breakpoints, respectively [24]. The low number of KPC-producing isolates is a limitation of the study, but the set of clinical isolates tested was representative of the population of KPC-producing isolates cultured from clinical specimens between 2010 and 2017 in Poland.…”
Section: Discussionsupporting
confidence: 86%
“…Of note, soon after the introduction of NDM in the country, the EuSCAPE project conducted between November 2013 and April 2014 in 10 hospitals all over Greece found it to rank as the second most frequent carbapenemase [ 5 ]. This was also reported by a subsequent nationwide multicentre study during the period 2014–2016 [ 20 ], indicating further dissemination. Moreover, according to a report published in 2015 [ 21 ], while KPC-2 production provides Enterobacteriaceae with intermediate resistance or even decreased susceptibility to meropenem in many cases, NDM-1 production allows HLR to meropenem.…”
Section: Discussionsupporting
confidence: 82%
“…CZA demonstrates high in vitro activity against nonmetallo-β-lactamase-producing K. pneumoniae strains in Greece [8]. To date, there are two reports on sporadic cases of CZA resistant K. pneumoniae from Greece, due to the production of KPC-23 [10], or VEB-25 [5].…”
Section: Discussionmentioning
confidence: 99%
“…CZA MICs (tested with a fixed avibactam concentration of 4 mg/L) ranged from 32 to 64 mg/L (Supplementary Table 1). PCR and sequencing analysis [8], showed that all isolates harboured bla KPC-2 as the sole carbapenemase gene. In addition to KPC-2, all eight isolates produced sulfhydryl reagent variable β-lactamase (SHV)-11, OXA-10, Temoniera β-lactamase (TEM)-1 and an extended spectrum β-lactamase (ESBL) of VEB-type.…”
Section: Microbiological and Molecular Analysesmentioning
confidence: 98%
See 1 more Smart Citation